Application of flow cytometry for myelodysplastic syndromes: Pitfalls and technical considerations. Issue 4 (14th December 2015) - Alhan, Canan; Westers, Theresia M.; Cremers, Eline M. P.; Cali, Claudia; Ossenkoppele, Gert J.; van de Loosdrecht, Arjan A.
Abstract : The application of flow cytometry (FC) is recommended as part of the diagnostic approach for MDS. The complexity of flow cytometric analysis of bone marrow cells in MDS has been an obstacle for general application. However, in the past years several studies showed practical flow cytometric approaches for the diagnosis and prognosis of MDS. In this report we discuss technical considerations and highlight issues that require special attention when handling and analyzing bone marrow samples of patients with cytopenia and suspicion of MDS. © 2015 Clinical Cytometry Society